Density functional theory calculations, growth, structure, and optical properties of birefringent LiNaV2O6. Issue 4 (12th February 2016) - Kong, Qingrong; Yang, Yun; Liu, Lili; Bian, Qiang; Lei, Bing-Hua; Li, Linping; Yang, Zhihua; Su, Zhi; Pan, Shilie
Abstract: Abstract : A congruent melting compound LiNaV2 O6 has been synthesized by high-temperature solution reaction and it has been grown with sizes up to 11 × 6 × 2 mm 3 by the top-seeded growth method for the first time. LiNaV2 O6 crystallizes in the monoclinic system with space group C 2/ c, with a = 10.184(2) Å, b = 9.067(2) Å, c = 5.8324(11) Å, β = 108.965(14)°. UV–Vis–NIR diffuse reflectance spectrum of LiNaV2 O6 shows that it has a wide transmittance range from 385 to 2500 nm. The ab initio calculations show that the birefringence of LiNaV2 O6 is 0.136 at 589.3 nm. Therefore, LiNaV2 O6 may be a new birefringent material. Based on the analysis of the relationship between crystal structure and linear optical properties, it is found that the large birefringence is attributed to the particular arrangement of V–O anionic groups.